The Effect Of Level 1 Progressive Mobilization On Respiration Rate (Rr) Of Critical Patients In The Icu Room At Labuang Baji Hospital, Makassar - Asriadi; Irma Andrianys (Jurnal Life Birth, 2022)
Background: Critical patients who are treated in the ICU have various conditions that require the patient to receive maximum care. Level 1 progressive mobilization will affect oxygen saturation which can increase the frequency and depth of breathing, increase ventilation, decrease breathing and decrease breathing, and increase diaphragm expansion. Objective: To determine the effect of level 1 progressive mobilization on respiration rate (RR) in the ICU room at Labuang Baji Hospital, Makassar. Method: The research design used in this research is quantitative research with a pre-experimental research design with a one group pre-test post-test design. The sample used in this research was 16 respondents. This research was conducted on 19 July-19 August 2022 in the ICU room at Labuang Baji Hospital, Makassar. The research tool uses a respiration rate measuring device using a Bedside Monitor and an observation sheet. The analysis used is non-parametric statistics, namely the Wilcoxon Signed Rank Test analysis. Results: Analysis of the pretest respiration rate, namely an average value of 16x/minute, protest respiration rate, an average value of 22x/minute with a significance of 0.002 <0.05. Conclusion: There is an influence between Level 1 Progressive Mobilization on changes in the Respiration Rate value of the ICU room at Labuang Baji Hospital, Makassar.